2010
DOI: 10.4314/fje.v2i1.50792
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of tree planting programmes in Maiha Local Government area of Adamawa state, Nigeria

Abstract: Deforestation, soil degradation and other forms of environmental degradation that could lead to desert encroachment have become a major concern in the world more especially in the sub Saharan Africa. Consequently, environmentalist and agriculturalists have led a campaign on afforestation and agroforestry to control this problem. This paper appraises tree planting and tree planting programs in the study area. Primary and secondary data sets ware collected on the socio economic activities of people as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In cases of severe erosion, landslides, and other environmental disasters, people can die. These results are similar to those of Jibo et al (2020), Okorafor et al (2017), andEgboka et al (2019). All these studies agree with these results…”
Section: Discussion Environmental Degradation On Social Capital and I...supporting
confidence: 93%
See 2 more Smart Citations
“…In cases of severe erosion, landslides, and other environmental disasters, people can die. These results are similar to those of Jibo et al (2020), Okorafor et al (2017), andEgboka et al (2019). All these studies agree with these results…”
Section: Discussion Environmental Degradation On Social Capital and I...supporting
confidence: 93%
“…It was also found that environmental damage hurts homes and businesses, ruins farms with valuable crops, makes land useless for making money due to flooding and erosion, and takes away money that should have been used for building things or starting businesses. These findings match the results of studies conducted by Jibo et al (2020), Okorafor et al (2017), andEgboka et al (2019). Okorafor et al (2019) discovered that there is a notable connection between damage to the environment and the worth of properties that are affected by this damage in cities.…”
Section: Environmental Degradation On Economic Activitiessupporting
confidence: 88%
See 1 more Smart Citation
“…Landfills have been acknowledged as an appropriate method of organized solid waste disposal in urban areas. However, many countries are yet to adopt the strategy because of the technical expertise required in the design, operation, and monitoring process that will ensure compliance with environmental regulations [8,9,10,11]. Additionally, the increasing population densities and its resultant of less land availability for siting landfills coupled with environmental health concerns, are also difficulties to overcome.…”
Section: Introductionmentioning
confidence: 99%